I’dādu Mu’jami Ṣuhufiy “’Arabiy-Indūnīsiy wa Indūnīsiy ‘Arabiy” Mu’tamidan ‘alā Kitābi Lughatu al-Jarāidi: al-Tahaniy wa al-Ta’aziy wa Syatta al-I’lānāt - Shovi Maryam; Nurul Murtadho; Ali Ma’shum (Fakultas Tarbiyah Program Studi Pendidikan Bahasa Arab Institut Agama Islam Darullughah Wadda'wah Pasuruan, 2020)
This study aims to describe the characteristic and quality of Journalistic Arabic Dictionary. This study method has five development steps (1) analysis and data collection, (2) design, (3) development, (4) validation, and (5) revision. The result showed that the average level of product quality is very good in content and design according to validators, lecturer, and students of Arabic Literature in State University of Malang.